A dual RPA-LFD assay for the simultaneous detection of Salmonella typhimurium and Salmonella enteritidis - Liao, Chuan; Pan, Lele; Tan, Meiying; Zhou, Zihan; Long, Shaoping; Yi, Xueli; Li, Xuebin; Wei, Guijiang; Liang, Lina (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction:Salmonella was one of the most common bacteria that caused foodborne illness, with S. typhimurium (Salmonella typhimurium) and S. enteritidis (Salmonella enteritidis) infections accounting for more than 75% of human salmonella infections. Methods: In this study, we developed a method of dual recombinase polymerase amplification (RPA) combined with a lateral flow dipstick for the rapid detection of S. typhimurium and S. enteritidis in clinical specimens (stool). Results: The entire reaction process, including amplification and result reading, could be completed within 65 min. The detection limits of S. typhimurium and S. enteritidis in pure culture samples were 5.23 × 101 CFU/mL and 3.59 × 101 CFU/mL, respectively. The detection limits of S. typhimurium and S. enteritidis in artificially contaminated samples were 8.30 × 101 CFU/mL and 2.70 × 102 CFU/mL, respectively. In addition, the method had no cross-reaction with other pathogenic microorganisms. The results in clinical samples were fully consistent with those obtained using Bacterial Analysis Manual, with sensitivity and specificity were 100% (8/8) and 100% (17/17) for S. typhimurium and 100% (4/4) and 100% (21/21) for S. enteritidis, respectively. Discussion: The detection limits of S. typhimurium and S. enteritidis in artificially contaminated samples were higher than those in pure culture samples, which might be attributed to the inherent complex composition of artificially contaminated samples. In addition, the detection limits of S. typhimurium and S. enteritidis in the same sample were also different, which might be attributed to different amplification efficiency of two target genes in the same reaction system. Conclusion: This assay had potential application outdoors, as it could be performed within 1 h at 38°C without a complex instrument, and the results could be observed with the naked eye. In conclusion, the dual RPA-LFD assay established in this study had practical significance for the rapid detection of S. typhimurium and S. enteritidis in the future.